“Life as Suffering”: the Motive of Revenge in the Novel by E. T. A. Hoffmann “The Marquis de la Pivardière” and the Novel by J. Janin “The Dead Donkey and the Guillotined Woman” - N. M. Ilchenko; Yu. A. Marinina (Научный диалог, 2021)
The motive of revenge is analyzed on the basis of the French topos, considered as a space of crime and punishment. It is noted that the novel by E. T. A. Hoffmann and the novel by J. Janin are united by attention to fate as a catastrophic concept inscribed in the picture of life in France. The relevance of the study is associated with the problems of the formation of national identity, national image by romantics of Germany and France. It is shown that the German romantic, who relied on fantasy as a means of understanding and cognizing life, became a model for J. Janin in the perception of “observed material”. Special attention is paid to the artistic embodiment of life as an “ugly abyss” in which the heroines of E. T. A. Hoffmann and J. Janin find themselves. The results of a comparative analysis of the novel, the action of which belongs to the second half of the 17th century are presented in the article. But the writer discusses the morals of the heroes from the point of view of the romantic canon, and the novel, the action of which is attributed to the end of the 20s of the 19th century. The novelty of the research is connected with the fact that the drama of human existence (female) is viewed as a result of the fragility of earthly existence, the loss of faith in the rationality of the universe. This approach made it possible to analyze the national forms of romanticism, the individual approach of Hoffmann and Janin to understanding the moral and the sinful.